User-Designed Dementia Care Pathways. A disruptive approach to mapping dementia support services. (28th July 2017) - Carey, Daniel; Tennant, Andy; Rodgers, Paul; Dodd, Katie
Abstract: This paper reports on the first author's ongoing Arts and Humanities Research Council (AHRC) funded PhD research exploring the potential for disruptive design interventions within the context of health and social care. This paper describes an ongoing project to map the services available to people with dementia and their carers, with a specific emphasis on the services available before the patient receives a formal diagnosis of dementia. Many service users are simply unaware of the support available to them, and are left to navigate their own paths through the unfamiliar and intimidating landscape of dementia services. This paper reports on the development of two tools for use by carers, patients, and dementia service providers. These tools offer innovative ways of enabling service users to visualise the pathway of their current and future care, whilst also allowing service providers to identify the strengths and weaknesses in the type of support they provide.